Refugees and a local community : a study of aborted establishment of an asylum seeker center in Jämsä in 2010 - Jokinen-Jokela, Terhi (2010)
The focus of this thesis are the frames created and used throughout the examined time period from January 2010 to September 2010 and the news narrative created by the local newspaper, Jämsän Seutu, about a proposed establishment of youth refugee and asylum seeker center in Jämsä, Finland. The narrative is studied through the theoretical lenses provided by George Lakoff, Karina Horsti and Magdalena Jaakkola. In order to place the frames within the context of a small rural town of Jämsä and in order to gain insight on why certain frames are used and the possible reasoning behind the argumentations of the frames are then further examined through the theories of political science by Manuel Castells and Benedict Anderson. The study of the narrative is based on five routine news reporting articles, three columns, two general articles on refugees and multiculturalism and three letters to the editor.